2011
DOI: 10.1021/je100854j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Poly(ethylene oxide) 400 (PEG400) on the Absorption of CO2in Diethanolamine (DEA)/H2O Systems

Abstract: An experimental device coupling vaporÀliquid equilibrium (VLE) measurements and liquid phase analysis by Fourier transform infrared (FTIR) spectroscopy has been used to study the absorption of CO 2 in water/diethanolamine (DEA)/ poly(ethylene oxide) 400 (PEG400) systems. The concentration of the molecular form of absorbed CO 2 and the evolution of the carbamate species are measured with the IR spectroscopic method. The partial pressure of carbon dioxide and the liquid phase speciation have been determined at T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
(23 reference statements)
3
14
0
Order By: Relevance
“…Using FTIR for the in situ analysis of aqueous alkanolamine solutions has first been applied aiming at more accurate vapor-liquid equilibrium data for such systems. So far, this technique has been applied to equilibrium measurements of aqueous solutions of DEA [10,12,13,15] and MDEA [11,14].…”
Section: Inline Process Monitoring By Multivariate Analysismentioning
confidence: 99%
“…Using FTIR for the in situ analysis of aqueous alkanolamine solutions has first been applied aiming at more accurate vapor-liquid equilibrium data for such systems. So far, this technique has been applied to equilibrium measurements of aqueous solutions of DEA [10,12,13,15] and MDEA [11,14].…”
Section: Inline Process Monitoring By Multivariate Analysismentioning
confidence: 99%
“…Aqueous solutions of MDEA have been widely used for the removal of CO 2 form a variety of gas streams [9,10]. Besides the amine blends, adding a physical solvent to the aqueous solutions of alkanolamines is considered to be an effective method to lower the regeneration energy cost [11,12]. For example, Archane et al [11] studied the vapor-liquid equilibria, the concentration of the molecular form of absorbed CO 2 , the partial pressure of CO 2 and the liquid phase speciation for CO 2 -poly(ethylene oxide)400 (PEG400)-diethanolamine (DEA) aqueous solutions, and demonstrated the influence of PEG400 on the absorption of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the amine blends, adding a physical solvent to the aqueous solutions of alkanolamines is considered to be an effective method to lower the regeneration energy cost [11,12]. For example, Archane et al [11] studied the vapor-liquid equilibria, the concentration of the molecular form of absorbed CO 2 , the partial pressure of CO 2 and the liquid phase speciation for CO 2 -poly(ethylene oxide)400 (PEG400)-diethanolamine (DEA) aqueous solutions, and demonstrated the influence of PEG400 on the absorption of CO 2 . Their results showed that lower energy cost can be achieved in regeneration because at a given CO 2 loading and constant concentration of DEA, the CO 2 molecular concentration increases with the increase of PEG400 concentration, whereas the ion repartition is not significantly influenced by the solvent composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, when using the popularly applied MEA (monoethanolamine)aqueous solution as absorbent, the mass fraction of MEA must be no greater than 30% in order to lower the corrosion, thus large quantities of superheated steam are needed in the regeneration tower to heat the 70% residual water. To lower the energy cost, many new absorbents have been developed in recent years [6,7], e.g., MEA promoted MDEA (N-methyldiethanolamine) aqueous solution. MDEA has the advantages of high resistance to thermal and chemical degradation, and low corrosivity [8].…”
Section: Introductionmentioning
confidence: 99%